Synthesis and evaluation of novel sulfonamide analogues of 6/7-aminoflavones as anticancer agents via topoisomerase II inhibition. Issue 14 (15th July 2020) - Shelke, Rohini N.; Pansare, Dattatraya N.; Sarkate, Aniket P.; Narula, Ishudeep K.; Lokwani, Deepak K.; Tiwari, Shailee V.; Azad, Rajaram; Thopate, Shankar R.
Graphical abstract: Abstract: A series of new sulfonamide analogues of 6/7-aminoflavones were synthesized by using molecular hybridization approach. These new sulfonamide analogues were screened for antiproliferative activity against human hepatocellular carcinoma (HepG-2), human lung cancer cell line (A-549), human colorectal adenocarcinoma (Caco-2) cancer cell lines. Compounds 5p, 5q, 5t, 5v, 5w and 5x exhibited good anticancer activity against selected cancer cell lines. These compounds were further evaluated to predict their ability to inhibit topoisomerase-II enzyme. Compound 5x has shown potent antiproliferative activity (IC50 value 0.98 µM) as compared to standard drug Adriamycin (IC50 = 0.94 µM) indicating that these compounds exhibits anticancer activity via inhibition of topoisomerase-II enzyme. Docking results also have supported above observations by indicating that compounds are held in the active pocket by combination of various hydrogen and hydrophobic interactions with Top II-DNA-etoposide enzyme.